STIM and Orai1 Variants in Store-Operated Calcium Entry - Rosado, Juan A.; Diez, Raquel; Smani, Tarik; Jardín, Isaac (Frontiers in Pharmacology, 2016)
Store-operated Ca2+ is an ubiquitous mechanism for Ca2+ entry in eukaryotic cells. This route for Ca2+ influx is regulated by the filling state of the intracellular Ca2+ stores communicated to the plasma membrane channels by the proteins of the STIM family, STIM1 and STIM2. Store-dependent, STIM1-modulated, channels include the Ca2+ release-activated Ca2+ (CRAC) channels, comprised of subunits of Orai proteins, as well as the store-operated Ca2+ (SOC) channels, involving Orai1 and members of the canonical transient receptor potential (TRPC) family of proteins. Recent studies have revealed the expression of splice variants of STIM1, STIM2 and Orai1 in different cell types. While certain variants are ubiquitously expressed, others, such as STIM1L, show a more restricted expression. The splice variants for STIM and Orai1 proteins exhibit significant functional differences and reveal that alternative splicing enhances the functional diversity of STIM1, STIM2 and Orai1 genes to modulate the dynamics of Ca2+ signals.